Early Haemorrhage Postpartum (HPP); With Complication Disseminated Intravascular Coagulation, Sepsis, Acute Kidney Injury - Oktavian, Rizki; Gunawan Efri; Sriyanti, Roza; Taslim, Emilzon (Andalas Obstetrics And Gynecology Journal, 2024)
Background : Hemorrhage Postpartum (HPP) is the leading cause of maternal death worldwide with an incidence of 5%-10% of all deliveries. 70% of cases of HPP are caused by atony of the uterus. If HPP is not handled properly, it will cause worsening of the patient's condition which causes various multiorgan complications. Objectives : To discuss the management of HPP cases complicated by DIC, sepsis and AKI. Method : case report. Case : A female patient, 36 years old, was referred from a private hospital to PONEK RSUP Dr. M. Djamil Padang with a diagnosis of decreased consciousness ec suspected sepsis in post SCTPP oi used SC 2x + post relaparotomy oi bleeding subfascia + moderate anemia. After surgery, the patient looked pale and the hemoglobin was 7, then relaparotomy was done and done B-lynch oi uterine hypotony. After relaparotomy, the patient experienced worsening then referred to the hospital. The patient arrives with hipovolemic shock + AKI + Sepsis + DIC , then the condition improvement is carried out in ROI and hysterectomy relaparotomy is performed. The patient has worsened, maximum treatment has been carried out from the intersivist, but the patient's condition continues to worsen and eventually dies.Conclusion : Early diagnosis and rapid treatment through a multidisciplinary team and the availability of an Intensive Care Unit (ICU) can prevent complications and reduce morbidity and mortality.